Mothers' observed reminiscing style and children's emotion regulation: an examination of cross-lagged effects - Çetin, Deniz; Steinsbekk, Silje; Van der Kaap-Deeder, Jolene (Frontiers in Developmental Psychology, 2026)
How mothers talk about emotional memories relates to their children's socioemotional development. However, there is a limited understanding of how this reminiscing relates to children's emotion regulation. Similarly, we know little about whether children's emotion regulation shapes how mothers reminisce. Therefore, in this study we examined the cross-lagged relations between mothers' observed reminiscing style (autonomy support, elaboration, and positive and negative evaluation) and children's emotion regulation. Twice, mother and child (Mage = 4.02 years, SD = 0.85, 47.2% female) pairs reminisced about a positive and a negative memory (T1, n = 89; T2, n = 63)—with 7 months apart. Additionally, at both timepoints, mothers completed a questionnaire assessing their child's emotion regulation skills. Through structural equation modeling, we found that during negative memory conversations, mothers positively evaluating their child's contributions was related to more adaptive emotion regulation in children across time. Regarding the opposite direction of influence, children's high emotional lability negatively related to mothers' autonomy support 7 months later, especially in the context of positive memories. There were no cross-lagged relations between mothers' elaboration or negative evaluation of children's contributions and child emotion regulation. Nevertheless, our findings suggest that parent-child reminiscing and children's emotion regulation mutually influence each other.